Signaling in Minilaterals in the Indo-Pacific: The Cases of Quad and AUKUS (2017-2022) - Poornima Vijaya (Journal of Liberty and International Affairs)
This article examines the coalition-building efforts of the Quad and AUKUS through the lens of strategic signaling, arguing that minilateral coalitions employ signaling tactics through various means to achieve a common goal. The case studies of Quad and AUKUS demonstrated differences in their strategic signaling. However, their goals are carefully formulated. This article uses discourse analysis to find that the Quad signaled an ambitious “Free and Open Indo-Pacific” as a positive force for the region’s security and prosperity. AUKUS, on the other hand, signaled military cooperation as a balance of power amidst an assertive China. While minilateralism is growing in the 21st-century multipolar world, this article examines how these emerging trends of issue-based coalitions, flexible alignments, and informal alliances create avenues for like-minded countries to strengthen capacity-building measures.